Literacy Learning Cohorts: Content-Focused Approach to Improving Special Education Teachers' Reading Instruction. (January 2017) - Brownell, Mary; Kiely, Mary Theresa; Haager, Diane; Boardman, Alison; Corbett, Nancy; Algina, James; Dingle, Mary Patricia; Urbach, Jennifer
Two professional development (PD) models for teachers were compared on teacher and student outcomes. Special education teachers participated in Literacy Learning Cohorts (LLC), a PD innovation designed to improve content and pedagogical knowledge for providing reading instruction to upper elementary students with learning disabilities. The LLC, based on Desimone's (2009) framework, included 2 days of initial PD with follow-up meetings, coaching, and video self-analysis. A comparison group received only 2 days of PD. Results of independent t tests and analyses of covariance indicated that LLC teachers demonstrated significant change in instructional time allotted to, and quality of, word study and fluency instruction. LLC teachers also made significantly greater gains on the fluency knowledge measure as compared with the comparison group, but they did not differ in word study knowledge. Hierarchical linear modeling analyses showed that students of LLC teachers made significantly greater gains on word attack skills and decoding efficiency than did students of teachers in the comparison group.